The Effect of Chemical Disinfectants on the Color of a Porcelain Shade Guide - ArRejaie, Aws Saleh (International Journal of Health Sciences, 2014)
Objective: To evaluate the effect of long term utilization of chemical disinfectants on the color of porcelain shade guides. Methodology: three chemical disinfectants were used in this study: Minuten spray, Lysol ICQuaternary Disinfectant Cleaner (QDC), and Lysol IC Ready to Use Disinfectant Cleaner (RDC). Simulation of disinfecting cycles for one year, two years, and three years were done on Vita 3D master shade guide. Color differences were determined by visual inspection and analyzing ΔE. Results: ΔE values were significantly below the perceptible (ΔE=1) and the clinically acceptable (ΔE=3.7) thresholds. Conclusions: Simulated utilization of Minuten Spray, Lysol IC (QDC), and Lysol (RDC) disinfectants for up to three years didn’t cause a clinically significant difference in the color of VITA Toothguide 3D-Master Shade Guide.